Diurnal variation of urinary markers of nucleic acid oxidation. (June 2014) - Grew, Ida S.; Cejvanovic, Vanja; Broedbaek, Kasper; Henriksen, Trine; Petersen, Morten; Andersen, Jon T.; Jimenez-Solem, Espen; Weimann, Allan; Poulsen, Henrik E.
Abstract Aims. Urinary 8-oxo-7, 8-dihydro-2ʹ-deoxyguanosine (8-oxodG) and 8-oxo-7, 8-dihydroguanosine (8-oxoGuo) are biomarkers of oxidative stress with clinical potential in a variety of diseases. As part of their clinical validation, this study aimed to investigate whether the urinary excretion of 8-oxodG and 8-oxoGuo undergoes diurnal variation and to evaluate the validity of 6-hour sampling as well as creatinine corrected spot urine sampling. Methods. A total of 23 healthy study subjects collecting their 24-h urine in four fractions covering 6 hours each. Urinary 8-oxodG and 8-oxoGuo levels were quantified using a modified version of UPLC-MS/MS. Results. No significant difference in excretion levels between the 12-h diurnal and 12-h nocturnal state or between the four 6-h periods during the day was found for either biomarker. A strong linear relationship between the excretion levels in each of the 6-h periods and the 24-h excretion level was shown for both biomarkers. Creatinine correction of the 6-h levels reduced the biological variation of the excretion levels and weakened the linear relationship with the uncorrected 24-h excretion level for both biomarkers. The correlations were strengthened when the 24-h excretion level was expressed per kg body weight. Conclusion. The results showed that 8-oxodG and 8-oxoGuo did not undergo diurnal variation in the study population overall and hence that the time of sampling is not crucial. Furthermore, 6-h sampling can be used as a substitute for 24-h sampling, and creatinine corrected sampling may be rational due to the reduction in biological variation of the biomarkers and the reasonable correlation with body weight-adjusted 24-h levels.